Timber production of Nothofagus pumilio forests by a shelterwood system in Tierra del Fuego (Argentina) - Martínez Pastur, Guillermo José (2000)
Nothofagus pumilio is the most important timber native species from south Patagonia of Argentina and Chile. The total volume and timber production vary according to site quality, stocking, growth phase and previous land management. The aim of this work was to evaluate the existence and the productive potential of wood for the sawmill industry in a shelterwood seed cut of N. pumilio forests along the range of site classes. Sample plots were established in 3 ha of an old-growth virgin forest without regeneration patches (SDI 95-131%) along the five classes of site (I-V). Total stand volumes varied from 400 to 1100 m3/ha and volume density index (ratio of total volume over basal area) varied from 6 to 14 m3/m2. The volume yield present differ significantly among site qualities with log volumes between 40 and 400 m3/ha. The number of timber logs decreases from the better sites towards the worst (800-200 logs/ha), as well as their volume average (0.5-0.2 m3/log). Several published studies in timber production were compared and discussed with the obtained results. Considering new alternatives in the N. pumilio timber management allow managers to obtain higher harvesting indexes, increasing the benefits for the forest company and diminishing the annual wood areas necessary to supply the requirements of the sawmills in Tierra del Fuego.